Science and Technology for the Community: Empowering Housewives through the Production of Aromatherapy Candles Made from Used Cooking Oil - Aulia Nur Febrianti; Erry Ika Rhofita (Fakultas Pertanian, 2026)
This community service program (Iptek bagi Masyarakat) is way to empower housewives through the utilization of used cooking oil into aromatherapy candles as an environmentally friendly and economically valuable household waste management effort. The background of this activity based on environmental issues in RT 03 RW 03, Amir Mahmud Urban Village, Gunung Anyar District, Surabaya City, particularly related to improper waste management and the disposal of used cooking oil. Based on questionnaire results, most residents still dispose of used cooking oil into drainage systems (76.2%) and do not consistently separate organic and inorganic waste. The method used in this program is Participatory Action Research (PAR), which actively involves the community in all stages, including problem identification, planning, implementation, and evaluation. The activities were carried out through socialization on waste management, training on the production of aromatherapy candles, and assistance in the production and packaging processes. The results indicate there is increasing in knowledge and skills among housewives in processing used cooking oil into valuable products. moreover, the program enhances community awareness of proper waste management and creates opportunities for environmentally-based small businesses. Therefore, this program is expected to contribute to improving environmental quality and community welfare in a sustainable manner.